2003
DOI: 10.1016/s0012-1606(03)00177-5
|View full text |Cite
|
Sign up to set email alerts
|

DLX5 positions the neural crest and preplacode region at the border of the neural plate

Abstract: The neural crest and sensory placodes arise from a region of the embryonic ectoderm that lies between the neural plate and future epidermis. While some of the signalling pathways that are involved in cell fate determination at the border of the neural plate have been characterised, it is still unclear how different signals are integrated. Transcription factors of the DLX gene family that may mediate such cell fate decisions are expressed at the border of the neural plate. Here, we demonstrate that DLX5 is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
181
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(196 citation statements)
references
References 84 publications
13
181
2
Order By: Relevance
“…These cells are presumably neural crest-derived, although expression in resident non-neural crest mesenchyme cannot be excluded. While DLX5 expression has been found along the border of the chick neural plate prior to crest cell migration (McLarren et al, 2003), we did not detect β-gal staining or Cre expression within the hindbrain or in streams extending from the hindbrain towards the pharyngeal arches. This supports previous studies in which neither Dlx5 nor Dlx6 expression has been observed in premigratory neural crest cells (Acampora et al, 1999;Depew et al, 1999;Robledo et al, 2002;Zerucha et al, 2000).…”
contrasting
confidence: 89%
“…These cells are presumably neural crest-derived, although expression in resident non-neural crest mesenchyme cannot be excluded. While DLX5 expression has been found along the border of the chick neural plate prior to crest cell migration (McLarren et al, 2003), we did not detect β-gal staining or Cre expression within the hindbrain or in streams extending from the hindbrain towards the pharyngeal arches. This supports previous studies in which neither Dlx5 nor Dlx6 expression has been observed in premigratory neural crest cells (Acampora et al, 1999;Depew et al, 1999;Robledo et al, 2002;Zerucha et al, 2000).…”
contrasting
confidence: 89%
“…Furthermore, AP2γ has redundant activities with AP2α in neural crest induction and nonneural ectoderm derivative development [26]. Other factors such as Pax7, Msx1, Zic1, Dlx5 and AP2α were shown as neural border specifiers [30,[63][64][65][66][67][68]. During early neuralization of the chick embryo, some factors are mainly expressed in the peripheral (Pax7, Dlx5 and AP2α) or caudal (Msx1) ectoderm and the expressions of others (Zic1) partially overlaps with cSox2 expression [68].…”
Section: Discussionmentioning
confidence: 99%
“…2C) (Mishima and Tomarev, 1998;Esteve and Bovolenta, 1999;Sahly, et al, 1999;Kobayashi, et al, 2000;Pandur and Moody, 2000;McLarren, et al, 2003;Bessarab, et al, 2004;Schlosser and Ahrens, 2004;Litsiou, et al, 2005). Simultaneously, precursors for all placodes become concentrated in the Six/Eya + territory to form a contiguous, unique domain: the preplacodal region (Streit, 2002;Bhattacharyya, et al, 2004) (Fig.…”
Section: Subdivision Of the Ectoderm: Changes In Gene Expression And mentioning
confidence: 99%
“…FoxiI ) the ectoderm next to the neural plate. Thus, at early neurula stages a contiguous stripe of ectoderm coexpresses pre-neural and non-neural ectoderm markers and has therefore been termed the 'border' (Streit and Stern, 1999;McLarren, et al, 2003;Woda, et al, 2003;Meulemans and Bronner-Fraser, 2004). Within the border region precursors for neural, neural crest, epidermis and placodes remain interspersed (Kozlowski, et al, 1997;Streit, 2002;Bhattacharyya, et al, 2004).…”
Section: Subdivision Of the Ectoderm: Changes In Gene Expression And mentioning
confidence: 99%